Uji Aktivitas Ekstrak Herba Sambiloto (Andrographis paniculata (Burm.f.) Ness) Terhadap Kadar Nitrogen Monoksida Pada Mencit Putih Jantan Hiperkolesterolemia - Aried Eriadi; Suhatri Suhatri; Nindywaii Honolhulu (Jurnal Farmasi Higea, 2017)
Effect of extract of bitter herbs (Andrographis paniculata (Burm.f.) Ness) has conducted research on the levels of NO in hypercholesterolemic male white mice. Hypercholesterolemia was induced by high-fat foods and propylthiouracil. Bitter herbs extract was administered orally every day for 60 days with a dose of 25 mg/kg BB, 50 mg/kg BB, and 100 mg/kg BB. The negative control group was only given regular meals and a positive control group was given a high-fat foods and propylthiouracil. Parameters measured were the levels of NO in serum. The results showed that the extract of bitter herbs can increase blood levels of NO white male mice when compared to the positive control (hypercholesterolemia), but still lower than the negative control (normal animals) (P<0.05). While the old factor does not affect the administration of organ weight ratio of the heart, liver and kidneys and significantly (P>0.05).